2017
DOI: 10.1371/journal.pone.0167273
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Activities of Blood Thiamine Diphosphatase and Monophosphatase in Alzheimer's Disease

Abstract: BackgroundThiamine metabolites and activities of thiamine-dependent enzymes are impaired in Alzheimer’s disease (AD).ObjectiveTo clarify the mechanism for the reduction of thiamine diphosphate (TDP), an active form of thiamine and critical coenzyme of glucose metabolism, in AD.MethodsForty-five AD patients clinically diagnosed and 38 age- and gender-matched control subjects without dementia were voluntarily recruited. The contents of blood TDP, thiamine monophosphate (TMP), and thiamine, as well as the activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Therefore, having demonstrated that the cKO mice displayed neuronal loss and brain atrophy, as well as many other pathophysiological features of AD, our study strongly supports that TPK deficiency and the consequent impairment in thiamine metabolism in the brain constitute a pathogenic factor that underlies multiple pathophysiological features of AD and plays a critical role in disease pathogenesis. Ours and another previous study have shown that TPK activity was not significantly changed in brain and blood samples of AD patients compared to control subjects 18,19 . It is possible that the existing method of TPK activity measurement was insensitive due to the condition of optimal pH and Mg2+ concentration, as well as abundant substrates (ATP and thiamine).…”
Section: Discussionsupporting
confidence: 43%
“…Therefore, having demonstrated that the cKO mice displayed neuronal loss and brain atrophy, as well as many other pathophysiological features of AD, our study strongly supports that TPK deficiency and the consequent impairment in thiamine metabolism in the brain constitute a pathogenic factor that underlies multiple pathophysiological features of AD and plays a critical role in disease pathogenesis. Ours and another previous study have shown that TPK activity was not significantly changed in brain and blood samples of AD patients compared to control subjects 18,19 . It is possible that the existing method of TPK activity measurement was insensitive due to the condition of optimal pH and Mg2+ concentration, as well as abundant substrates (ATP and thiamine).…”
Section: Discussionsupporting
confidence: 43%
“…Fourth, is brain glucose hypometabolism due to TDP reduction associated with other pathophysiological features of AD, such as tau hyperphosphorylation, neuroinflammation, insulin resistance, and microvascular dysfunction? Finally, our previous study showed that enhanced activities of phosphatases contribute to TDP reduction in AD [ 41 ]. What is the mechanism?…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent case-control study of humans showed that blood thiamine diphosphate concentration was significantly reduced in patients with AD relative to controls and had an AUROC of 77.4%, sensitivity of 78.1%, and specificity of 77.2% (125). A subsequent study reported that thiamine phophatases are increased in the blood of patients with AD, which may explain the low thiamine diphosphate concentration in AD (126).…”
Section: Current Status Of Knowledgementioning
confidence: 97%